Batik, A Beautiful Cultural Heritage that Preserve Culture and Supporteconomic Development in Indonesia - Steelyana, Evi (Bina Nusantara University, 2012)
Batik is an icon nation for Indonesia. Batik has awarded as cultural heritage from UNESCO on October 2nd, 2009and it is significantly affected to batik industry afterward.The raising of batik industry caused some multiplier effects to economics and socio cultural in Indonesia. In many areas of industry, banking role has always beenthe man behind the scene. Banking role in Indonesia also gives some encouragement and be part of batik industry development. Many national event has been created by some banks to encourage SME in batik industry to market their product internationally. This paper will give a simple explanation how banking industry and batik industry get along together in Indonesia, especially in financial sector to enhance economics development and to preserve a nation culture.Research methodology in this paper is quantitative method. This paper will give a simple analysis through comparative analysis based on export value from batik industry, domestic use of batik,batik industry development and microcredit or loan from banking industry to SME in batik industry.Many people wearing batik to show how they do appreciate and belong to a culture.Batik also gives other spirit of nationalism which represent in Batik Nationalis.The role of batik in international diplomacy and in the world level gives significant meaning for batik as a commodity which preserve Indonesian culture. In a piece of batik cloth, embodied socio-cultural and economic values that maintain the dignity of a nation.Â